PENEGAKAN HUKUM PIDANA TERHADAP PENDIRIAN RUKO YANG TIDAK MEMILIKI SUMUR RESAPAN BERDASARKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 10 TAHUN 2006 TENTANG SUMBER DAYAAIR DAN SUMUR RESAPAN DI KECAMATAN TAMPAN KOTA PEKANBARU - Gevi Adinda Putri; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Development store in the Pekanbaru City require every store has at least one infiltration wells arranged in Pekanbaru City Regional Regulation No. 10 of 2006 on Water Resources and Infiltration Wells. But many societies still do not heed the rules and are not given criminal sanctions expressly set out in article 29 of the regional regulation. The purpose of this thesis, namely; First, criminal law enforcement to the establishment of a store that does not have absorption wells Based on Regional Regulation of Pekanbaru No. 10 of 2006 on Water Resources and Infiltration Wells in District Tampan Pekanbaru. Second, factors that become an obstacle in the establishment of the criminal law enforcement store that does not have absorption wells Based on Regional Regulation of Pekanbaru No. 10 of 2006 on Water Resources and Infiltration Wells in District Tampan Pekanbaru. Third, the efforts should be made to overcome the obstacles in the enforcement of criminal law against the establishment of a store that does not have absorption wells Based on Regional Regulation of Pekanbaru No. 10 of 2006 on Water Resources and Infiltration Wells in District Tampan Pekanbaru.Type of this research can be classified in sociological research, because in this research the author directly conduct the research on the location or point studied to provide complete and clear picture of the problems examined. This research was conducted at the Department of Spatial Planning and Building Pekanbaru, Unit Municipal police of Pekanbaru City and the store arround of District Tampan Pekanbaru. The population and the sample is a whole parties relating to the issues examined in this study, the data source that used, primary data, secondary data, and tertiary data, data collection techniques in this study with a questionnaire, interview and literature study.From the research there are three basic problems that can be inferred. First, criminal law enforcement to the establishment of a store that does not have absorption wells Based on Regional Regulation No. 10 of 2006 on Water Resources and Infiltration Wells has not run up as expected by the regional regulation. Secondly, a limiting factor in the enforcement of criminal law against the establishment of a store that does not have absorption wells Based on Local Regulation Pekanbaru City Number 10 Year 2006 on Water Resources and Infiltration Wells in District Tampan Pekanbaru they are the lack of socialization of the government, lack of supervision of law enforcement authorities, and the lack of public awareness and compliance with laws. Third, the effort that can be provided in overcoming factors inhibiting the enforcement of criminal law against a store that does not have absorption wells Based on Regional Regulation No. 10 of 2006 on Water Resources and Infiltration Wells is to disseminate to society by means of counseling about the regional regulation, assertiveness from officials or law enforcement authorities, and foster public awareness and compliance about laws. The advices of writer, first, services or related agencies should pay more attention to the future in order to supervise the establishment of the shop. Second, it provides criminal sanctions strictly to persons who commit a violation as well as protecting the perpetrator. Third, Raise awareness and knowledge society through counseling and others about the importance of absorption wells.Keywords: Law Enforcement - Local Rules - Infiltration Wells